La descentralización del empleo y de la residencia en las áreas metropolitanas de Barcelona y Madrid. Efectos sobre la movilidad urbana. - Cladellas, Joan Angelet (Urban, 2011)
Índice • Estado de la cuestión. • Tendencias recientes en la descentralización del empleo y de la residencia en el AMB y el AMM. • Conclusiones. • Bibliografía. Resumen Los procesos de descentralización metropolitana de viviendas y empleo y su incidencia en la congestión del tráfico han suscitado un amplio debate en la literatura reciente. Este artículo examina las tendencias recientes en la descentralización del empleo y la residencia en las áreas metropolitanas de Barcelona y Madrid y su incidencia en la movilidad intermunicipal. Las conclusiones muestran una tendencia clara de descentralización hacia los alfoces respectivos, aunque los empleos localizados fuera de las ciudades centrales todavía siguen muy por debajo de los porcentajes alcanzados en las ciudades norteamericanas. Esta descentralización es generadora de importantes aumentos en la demanda de movilidad intermunicipal. El proceso descrito evidencia en ambos casos la carencia de un planeamiento eficiente a la escala metropolitana o regional que persiga y consiga un mejor ajuste en la asignación territorial de empleo y residencia, subordinando el planeamiento local a estos objetivos supramunicipales. Por último, hace una valoración económica de los costes de las externalidades derivadas de estas disfunciones, que justificarían la necesidad de poner en práctica un sistema eficiente de planificación regional. Abstract The processes of metropolitan decentralisation of housing and employment and their effect on traffic congestion have stirred up a great deal of debate in recent literature. According to some authors, the duration and distance of commuting increase over the course of ti me and decrease when there is a greater territorial balance in the distribution of housing and workplaces. In line with this point of view, planning the location of activities is a necessary instrument in urban policy for taking on the problems of large cities and reducing the negative externalities. This article examines the recent trends in the decentralisation of employment and housing in the metropolitan areas of Barcelona and Madrid and their effect on inter-municipal mobility. The results of the analysis show a clear tendency in decentralisation towards the respective suburban areas, although jobs located outside the central cities are still way below the percentages shown for U.S. towns and cities. This decentralisation generates a high increase in the demand for inter-municipal mobility. The process described shows, in both cases, the lack of efficient planning at the metropolitan or regional level towards seeking and achieving a better adjustment in the territorial assignation of employment and housing by subordinating local planning to these supramunicipal objectives. Local planning has pursued mainly housingrelated aims, while the location of companies appears to obey different criteria. These are some of the factors, among others, which help to distort the local markets for land, housing and transport, and help to explain the peculiarity of the process described over the growing imbalance in the territorial assignation of employment and housing. Lastly, an economic appraisal is made of the costs of the externalities derived from these dysfunctions, which would warrant the need for implementing an efficient regional planning system.